Ж.Цэвээн Монголын боловсролд - Пунсалдулам, Бор (Historia Mongolarum, 2007)
Нэрт эрдэмтэн Ж.Цэвээний монголд орчин цагийн сургууль боловсролыг үүсгэн байгуулахад оруулсан хувь нэмрийн тухай өгүүлнэ. J.Tseveen is one of the important creators of the modern Mongolian science, educational system and schooling. In terms of time, his contribution to activities to education and science can be classified into two periods such as the times of Olnoo Orgogdson Mongol Uls (Publicly Ascended Mongolia of Bogdo Khaan) (1911-1932), and Ardyn Zasag (People’s Government) (1921-1932).